2019
DOI: 10.1111/myc.12948
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole therapeutic drug monitoring in clinical practice and longitudinal analysis of the effect of routine laboratory measurements on posaconazole concentrations

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…The univariate and multiple linear regression analysis both showed that lower PCZ concentrations were observed with decreasing albumin concentrations, which is in line with previous analysis ( Märtson et al, 2019b ; Sime et al, 2019 ). Although CRP level in the current study was negatively correlated with PCZ C min in the univariate analysis, multiple linear regression analysis did not reveal any statistically significant association, which is consistent with the findings of Märtson et al (2019a) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The univariate and multiple linear regression analysis both showed that lower PCZ concentrations were observed with decreasing albumin concentrations, which is in line with previous analysis ( Märtson et al, 2019b ; Sime et al, 2019 ). Although CRP level in the current study was negatively correlated with PCZ C min in the univariate analysis, multiple linear regression analysis did not reveal any statistically significant association, which is consistent with the findings of Märtson et al (2019a) .…”
Section: Discussionsupporting
confidence: 91%
“…However, no such association was observed in our hematological disorders patient. Although PCZ treatment is associated with liver function abnormalities ( Boglione-Kerrien et al, 2018 ), the effect of liver function on PCZ concentrations was not confirmed in our study, which is consistent with the results previously published by Märtson et al (2019b) . Collectively, these results indicate that it is difficult to predict PCZ concentration that we have to monitor trough concentration and adjust PCZ dosage according to the results.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…105 However, higher posaconazole concentrations are not uncommon. 187,188,190,195,198,199 Although the drug is well tolerated, dose reduction should be considered if adverse drug effects occur and the posaconazole concentration is >2.5 mg/L, with follow-up TDM recommended. As there is no established clear threshold concentration for toxicity, a caseby-case approach is suggested.…”
Section: Question 2 What Are the Present Antifungal Tdm Targets Sampling And Sample Type Time-to-resampling And Dose Adjustment?mentioning
confidence: 99%
“…Pharmacological advice on drug adjustment was applied only partially, due to a borderline concentration or overexposure without toxicity. 314 High-dose PSZ treatment (300 mg •2) with a target trough level .3 mg/L and spontaneous drug levels .3 mg/ L are associated with potential hepatic or cardiac safety issues requiring close monitoring. However, drug intensification is feasible with TDM and clinical surveillance.…”
Section: Psz Tabletsmentioning
confidence: 99%